Genomic epidemiology of syphilis reveals independent emergence of macrolide resistance across multiple circulating lineages - Mathew A. Beale (Nature Portfolio, 2019)
Syphilis is caused by the bacterium Treponema pallidum subspecies pallidum (TPA), and incidence has risen recently in many countries. Here, Beale et al. provide whole-genome TPA sequences from 73 clinical samples and show how antimicrobial resistance emerged independently in circulating lineages.